Transformasi Digital dalam Pengelolaan Aset Pemerintah pada Badan Keuangan dan Aset Daerah Kabupaten Takalar - Nasir Nasir (Universitas Methodist Indonesia, 2026)
Local government asset management is an important aspect in realizing accountable and transparent governance. However, in practice, asset management still faces various problems, such as administrative disorder, inaccurate data, and weak supervision. Along with the development of information technology, digital transformation is seen as a strategic solution to improve the quality of government asset management. This research aims to examine the implementation of digital transformation in government asset management at the Takalar Regency Regional Finance and Assets Agency and identify supporting and inhibiting factors in its implementation. This study uses a qualitative approach with a case study method. Data collection techniques were carried out through in-depth interviews, observations, and documentation studies. The results of the study show that the implementation of the regional asset management information system has improved administrative order, the quality of asset data, and the transparency and accountability of local government asset management. However, the implementation of digital transformation is not fully optimal because it is still faced with limited human resource competencies, work culture adaptation, and technology infrastructure support. Therefore, continuous efforts are needed to strengthen the capacity of apparatus, internal policies, and infrastructure to optimize the benefits of digital transformation in the management of local government assets.